Regional Unemployment in Spain - Disparities, Business Cycle and Wage Setting - Roberto Bande; Melchor Fernandez; Víctor Manuel Montuenga (European Regional Science Association (ERSA), 2005)
The existence and persistence of regional disparities is a common problem of many European economies. However, in Spain this fact exhibits a characteristic feature: a strong positive relationship with the business cycle. The analysis in this paper investigates the relationship between this distinguishing feature of the Spanish economy with the wage bargain system, and how changes in this system may have influenced the aggregate Spanish labour market performance in the recent past. The empirical findings of an important imitation effect in wage bargainings may explain both the persistence of disparities and their positive relationship with the cycle. This result has a direct implication to employment policies, which must take into account the regional dimension of the unemployment problem.
Keywords: 330